Today will be different eaudiobook - Semple, Maria (2016)
A brilliant novel and instant New York Times bestseller from the author of Where'd You Go, Bernadette , about a day in the life of Eleanor Flood, forced to abandon her small ambitions and awake to a strange, new future. Eleanor knows she's a mess. But today, she will tackle the little things. She will shower and get dressed. She will have her poetry and yoga lessons after dropping off her son, Timby. She won't swear. She will initiate sex with her husband, Joe. But before she can put her modest plan into action, life happens. Today, it turns out, is the day Timby has decided to fake sick to weasel his way into his mother's company. It's also the day Joe has chosen to tell his office — but not Eleanor — that he's on vacation. Just when it seems like things can't go more awry, an encounter with a former colleague produces a graphic memoir whose dramatic tale threatens to reveal a buried family secret. Today Will Be Different is a hilarious, heart-filled story about reinvention, sisterhood, and how sometimes it takes facing up to our former selves to truly begin living.